The Application Program of Smoking Free University Policy Campaign in Sisaket Rajabhat University - Tanaprat Thuksin; Chuthamat Nopparat; Tanapat Sriwarom (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background:These policy campaign were developed inlaw enforcement protection a non-smoking forsmoking freeuniversityby students union president.Method:This quasi-experimental research aimed toevaluate the application program of smoking free university policy campaign. To study the effect of thestudent leadership development program in the management of the smoking free university, Sisaket RajabhatUniversity and study the level of participation of the student leaders in the management of the smoking freeuniversity towards the smoke-free zone in Sisaket Rajabhat University. by selecting the students unionpresident population of 20 people, the samples were selected according to the inclusion criteria and theexclusion criteria, which the research pattern was used to conduct a comparative study within One GroupPretest - Posttest Design in 12 weeks with 4 activities. The data were collected by using questionnaires andusing descriptive statistics presented in the form of a frequency distribution. The data distribution is normal.They were presented with the statistical values of frequency, percentage, mean and standard deviation. Andtranslate the results into score values comparison of the mean, differences before and after the experiment.Within the experimental group using statistics : Paired Samples t-Test. Results: The results of the researchwere found that after the development of the experimental development program, the students’ leadershipin the management of the non-smoking university, knowledge, skills, social roles, imagination or conceptabout oneself, motivation / mindset Participation in the development of student leadership potential inthe management of the non – smoking university. Significantly better than before development (p <0.05).Conclusion: In conclusion of the study : Results of the Student Leadership Development Program inManagement of Smoking Free Universities, Sisaket Rajabhat University. It can cause success factors inmanaging the non-smoking university. In organizing smoking free zones in Sisaket Rajabhat University. Tobring about effective action and efficiency and developed as the non-smoking university model Includingcampaigning activities establishing a banner that announces the non-smoking area that covers the entireuniversity. To create participation of university students and the student leaders,The students union presidenthave a clear understanding of roles and duties in their work operations and have an action plan. They realizedthe importance of organizing the non-smoking zone in the university. There are regulations / measures toprevent and control smoking in non-smoking zones jointly agreed by the leaders. Established a mechanism tosupport the construction of the non-smoking area in Sisaket Rajabhat University. The measures are followedup and monitored, and implement a participatory and sustainable non-smoking university.